Determination of Information Quality, Organizational Culture and Digital Competence of Work Effectiveness Through the Web-Based Hospital Management Information System of Raja Ahmad Tabib Regional Hospital, Kepulauan Riau Province - Erisna Dewi Ariyani; Chablullah Wibisono; Nurhatisyah Nurhatisyah (International Journal of Economics, Commerce, and Management, 2024)
Nowadays, the utilization of a Web-based Hospital Management Information System has been implemented in Raja Ahmad Tabib Hospital of Pulau Riau Province, which not only has an impact on patient services but can also have an impact on the effectiveness of employee work in serving patients in the hospital, in order of study aims to determine the effectiveness of work through Web-based HMIS (SIMRS) by determining the Quality of Information, Organizational Culture and Digital Competence. This study will conduct data analysis through SEM-PLS (Structural Equation Modeling-Partial Least Square) software, which the test conducted by the researcher uses path analysis to test the pattern of relationships that can reveal the influence of variables or a set of variables on other variables, both direct and indirect influences. Based on the results of the research that has been conducted, the researcher found that there is a positive influence between Organizational Culture both on HMIS and on work effectiveness and organizational culture has a significant determination of work effectiveness through the utilization of Web-based HMIS. On the other hand, the quality of information and digital competence are not significant to Web-Based HMIS, although both are significant to work effectiveness. However, the determination of information quality and digital competence does not have an indirect relationship to work effectiveness through Web-based HMIS.